The Influence of Morality on Insights Based on Āyatullāh Jawādī Àmulī’s Commentarial Thought - Qasim Subhani Fakhr (حکمت اسرا)
From a religious point of view, man’s happiness is achieved through correct insights and beliefs as well as the character and behavior deriving from the primordial nature and in accordance with the religious law. As the character and behavior of people is the outcome of the kind of their insights and beliefs, it has also an impact upon them. Man’s behavior gradually brings about positive or negative qualities and innate dispositions. Negative qualities and innate dispositions produce an insight in conformity with them which sometimes leads to denial of obvious truths, while positive qualities and innate dispositions establish and reinforce innate and intellectual insights causing heart to become luminous with the light of knowledge and wisdom. Attachment to this world is the root of negative characters and behaviors and abstaining from attachment to this-worldly desires is the root of positive characters and behaviors. The Qur’an and Tradition (al-Sunna) have stressed the importance of this fact and originated a specific frame for thoughts of Muslim scholars, particularly mystics and philosophers on epistemology. Relying on of Āyatullāh Jawādī Àmulī’s thought, the present article explains this Qur’anic reality.